Molecular Characterization and Risk Factors of Carbapenem-Resistant Hypervirulent Klebsiella pneumoniae Isolated from Chinese Tertiary Hospital - Zhu R; Li J; Lian S; Li Y; Cai M; Cao Y; Xu X (Infection and Drug Resistance)
Rongping Zhu,1,* Ju Li,2,* Siyan Lian,2,* Yishan Li,3 Meili Cai,2 Yingping Cao,2 Xiaohong Xu2,4 1Department of Blood Transfusion, Fujian Provincial Hospital, Fuzhou University Affiliated Provincial Hospital, Fuzhou, Fujian, 350001, People’s Republic of China; 2Department of Laboratory Medicine, Fujian Medical University Union Hospital, Fuzhou, Fujian, 350001, People’s Republic of China; 3Anxi County Traditional Chinese Medicine Hospital, Quanzhou, Fujian, 362000, People’s Republic of China; 4Fujian Medical University Union Clinical College, Fuzhou, Fujian, 350001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaohong Xu; Yingping Cao, Department of Clinical Laboratory, Fujian Medical University Union Hospital, Fuzhou, Fujian, 350001, People’s Republic of China, Tel +86 13959192290 ; +86 13365910806, Email vancy1988@163.com; caoyingping@aliyun.comBackground: Therefore, the objectives of this study were to investigate the prevalence of carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-hvKp) in Fujian Medical University Union Hospital, identify their genetic characters, characterize their resistance profiles, and identify risk factors for their infection to improve prevention and treatment strategies for CR-hvKp in the area.Methods: Between January 2021 and January 2022, clinically identified carbapenem-resistant Klebsiella pneumoniae (CRKp) isolates were collected. A PCR assay was used to detect the K capsule type, virulence genes, carbapenemase genes, and membrane pore protein. ERIC-PCR was carried out for homology analysis. Antimicrobial susceptibility test was used to determine drug resistance. Logistic multivariate regression analysis was conducted to confirm the risk factors for CR-hvKp infection.Results: In total, 239 CRKp isolates were obtained. The virulence genes with the highest detection rates were mrkD, iucA, and rmpA2. Of these isolates, 54 (22.59%) carried both iucA and rmpA2, thus classifying them as CR-hvKp. All CR-hvKp isolates carried blaKPC. Furthermore, capsular serotypes K64 (94.44%) and K47 (3.70%) were detected. Resistance was observed against most common antibiotics, with the exception of complete sensitivity to ceftazidime-avibactam. ERIC-PCR indicated a potential clonal spread among CR-hvKp. Multivariate analysis found that changing beds was a risk factor for CR-hvKp infection.Conclusion: Currently, the hospital predominantly carries K64 CR-hvKp that harbors the blaKPC. Our study found that changing patient beds was an independent risk factor for CR-hvKp infection.Keywords: carbapenem-resistant, hypervirulent, Klebsiella pneumoniae, virulence, resistance, risk factor